Proceso Financiero en la Ferretería Gaibor - Gaibor Zambrano, Guido Jahir (2018)
Acerías y Ferretería Gaibor is the company chosen for the present case study, based on the theme of "Financial Process in the Gaibor Hardware Store" with the social reason in charge of Guido Vicente Gaibor Pizarro with the Ruc 1202628846001 currently active in economic activity. It has a headquarters located in Babahoyo - on Garcia Moreno streets between olmedo and flowers, and a local branch located in Babahoyo - on the University Road Citadel La Ventura. The type of taxpayer is a natural person obliged to keep accounting and is categorized by the SRI in PYMES class as a small business. It began its activities at the beginning of 2012 with its name as such, (although in the descriptions according to the SRI database they date from the year 2002 and a restart of its economic activities in the year 2007, since its name and economic activity the main one was another and changed over time), according to a description on the SRI website, the retail activity of hardware items is an economic activity, but complementary articles have been implemented that extend a little beyond their name. The company, in its vast majority of information and database, carries it out in a physical way, among the most notable activities that go hand in hand with the accounting area, the inventory can be mentioned, as well as the daily sales are recorded in written form. As they are generated, the purchases are required at the time of the lack of merchandise, the accounts receivable and accounts payable are carried in written form and in turn in digital files. In the present case study, it will be revealed how accurate is the way in which records and information are kept based on their economic activity, in such a way that senior management or administrators can see the outcome of the period in a reliable manner, and to be able to make decisions at any time through what is reflected in the financial statements.